Nurses’ perspectives on using mobile health applications in southeastern Iran: Awareness, attitude, and obstacles - Jahanpour Alipour; Yousef Mehdipour; Somayyeh Zakerabasali; Afsaneh Karimi (PLoS ONE, 2025)
Introduction Nurses and patients can now ensure access to qualified healthcare using the new opportunities of mobile health (mHealth) applications (or apps). To use its potential effectively, understanding nurses’ use of this technology is crucial. Here, we examined the awareness, attitudes, and obstacles to using mHealth apps among nurses. Methods We applied a descriptive-analytical cross-sectional study from 08/04/2023 to 05/10/2023. Cochran’s formula estimated the sample size of 267 nurses. The researchers used a researcher-made questionnaire for data collection. We used descriptive (mean, standard deviation, frequency, and percentage) and analytical (Pearson and Spearman correlation) statistics for data analysis. Results Most nurses use a smartphone (86%), have an Android operating system installed (82%), and believe that mHealth is useful for nursing (85%), but do not use it for patient care (70.8%). The mean score for awareness, attitude, and obstacles regarding mHealth were 3.74 ±  0.657, 3.49 ±  0.513, and 3.50 ±  0.597 respectively. There was a significant positive correlation between the nurses’ awareness and attitude (r = 0. 289, P < 0.05) and nurses’ awareness and obstacles to using mHealth (r = 0. 171, P < 0.05), but a significant negative correlation between nurses’ attitude and obstacles (r = -0. 031, P < 0.05). Conclusion Despite nurses’ relatively favorable awareness and positive attitude towards the use of mHealth apps, most of them use these technologies for purposes other than patient care. Nurses considered patients’ lack of digital health literacy (DHL) and reluctance to use these technologies as the main obstacles to using mHealth apps. Improving the DHL of users (nurses and especially patients) and providing them with free access to mHealth apps is essential. Ensuring security and making the applications easy to use, as well as educating users, are also important factors. Furthermore, promoting nurses’ understanding of the benefits of mHealth and increasing their willingness to use these technologies is crucial.